Global, Regional, and National Trends of Chagas Disease from 1990 to 2019: Comprehensive Analysis of the Global Burden of Disease Study - Sergio Alejandro Gómez-Ochoa; Lyda Z. Rojas; Luis E. Echeverría; Taulant Muka; Oscar H. Franco (Global Heart, 2022)
Background: Chagas disease (CD) is a neglected tropical disease, endemic in Latin America, but due to migration and environmental changes it has become a global public health issue. Objectives: To assess the global prevalence and disability-adjusted life years due to CD using findings from the Global Burden of Disease Study 2019. Methods: The Global Burden of Disease data was obtained from the Global Burden of Disease Collaborative Network; results were provided by the Institute for Health Metrics and Evaluation. The prevalence and disability-adjusted life-years (DALYs) were described at a global, regional, and national level, including data from 1990 to 2019. Results: Globally, CD prevalence decreased by 11.3% during the study period, from 7,292,889 cases estimated in 1990 to 6,469,283 in 2019. Moreover, the global DALY rate of CD decreased by 23.7% during the evaluated period, from 360,872 in 1990 to 275,377 in 2019. In addition, significant differences in the burden by sex, being men the most affected, age, with the elderly having the highest burden of the disease, and sociodemographic index (SDI), with countries with the lowest SDI values having the highest prevalence of the disease, were observed. Finally, the prevalence trends have followed different patterns according to the region, with a sustained decrease in Latin America, compared to an increasing trend in North America and Europe until 2010. Conclusion: The global burden of CD has changed in recent decades, with a sustained decline in the number of cases. Although the majority of cases remain concentrated in Latin America, the increase observed in countries in North America and Europe highlights the importance of screening at-risk populations and raising awareness of this neglected tropical disease.